Is there any relationship between Red blood cell distribution width and Prognosis of brain death? - Sanaz Dehghani; Elahe Pourhosein; Amir Ali Hamidieh; Zeinab Mansouri; Niloufar Tirgar; Fariba Namdar; Pantea Ramezannezhad; Arefeh Jafarian; Marzieh Latifi (Babol University of Medical Sciences, 2023)
Background: Accumulating evidence has demonstrated that RDW (red blood cell distribution width) may independently predict clinically important outcomes in many populations. However, the role of RDW has not been elucidated in brain death. We conducted this study with the aim of evaluating the predictive value of RDW in brain death. Methods: A retrospective study of seventy-seven of brain death cases during 36 months were evaluated at university hospitals, affiliated in Tehran, Iran. Demographical data include age, sex, BMI and cause of brain death, also laboratory results (red blood cell distribution, mean corpuscular volume, hemoglobin) collected by checklists from patient records. Having the three RDW measurements (days of hospital admission, day of brain death, and day of cardiac arrest) required. Results: Time interval from hospital admission until brain death was 5.27±4.07. The mean age of brain death cases was 32.65±16.53. The mean RDW values on days of hospital admission, the day of brain death, and the day of cardiac arrest were 14.53±1.98, 15.12±1.93 and 15.18±2.07, respectively. Results of the repeated-measures ANOVA test reveal that RDW level was constantly higher in the traumatic patient group compared to the non-traumatic ones (P=0.008). Conclusion: The frequency of brain death was high in patients with high RDW values. RDW might be a prognostic biomarker for brain death. More prospective studies with large sample size and long follow-up period should be carried out to determine the prognostic significance of RDW and brain death in future.